HOW KINDERGARTEN PUPILS SAY “THANKS”: SOCIOLINGUISTIC ANALYSIS IN LANGUAGE TEACHING - Yuniah Budiarti (Center of Language and Cultural Studies [CLCS], 2018)
The study used qualitative design, focusing on how pupils of kindergarten express thank. The subjects of this study were 32 pupils in AL IHSAN Kindergarten Tenggarong and data were collected using observation, interview, and questionnaire. Data for this study were an expression of gratitude delivered using the word “thank” identified from three stimulations. Data were analyzed qualitatively focusing on inferences of context when the word “thank” was uttered and results of interview and questionnaire were clarified. This study discovered that the way pupils of kindergarten on Al Ihsan school communicate to express gratitude vary from explicit manner or smile. The word “thank” may be changed into “terima kasih” in Indonesian version and “jazakumullah” in Arabic. Not all pupils use the word “thank” however. Factors that influence the pupils to say “thank” include affective factors, internal and external. Internal factors are a feeling of embarrassment and mood at that time. External factors are the condition and the situation when they receive the gifts and the way how people gave them the gifts. The pupils’ parents background didn’t give an impact by automatically to the pupils by using the expression thank.